Bioequivalence of Two Formulations of Amoxicillin in Human Healthy Volunteers on (HPLC) Technique - Alaa K. Jabbar Alhamd (College of Pharmacy University of Baghdad, 2017)
Amoxicillin is commercially available in the form of capsules and tablets containing 250mg or 500mg for oral administration. It is also available in the form of suspension containing "25mg/mlâ€ . Amoxicillin is presently used as the most common antibiotics .Ten healthy Human volunteers were characterized respected to their pharmacokinetic and bioavailability of two formulations of Amoxicillin from two sources of  industrial companies  after a single dose administration was given orally. A procedure is described for determination the concentration levels of Amoxicillin in human plasma of healthy volunteers using high performance liquid chromatography (HPLC) with reversed-phase isocratic column at low wave length of UV-visible detection "230nm". An efficient drug extraction procedure was used for the separation of Amoxicillin after simple extraction with cold methanol using ODS-C18-DB column. The pharmacokinetic 500mg of Amoxicillin capsule orally administrated treatment through 10 hours  has been examined.  The  Amoxicillin  was eluted  for "10.0 minutes" at flow Rate "1.5ml/min." and Temperature equal to 298 K .The retention time of Amoxicillin was observed at 7.0 minutes. The mean absolute recovery of Amoxicillin in blood plasma of all healthy volunteers were 94.1% at 1.0ppm, 102% at 5.0ppm, 103% at 10.0ppm 102% at 20ppm, 99.3% at 40ppm and 104% at 50ppm respectively. The assay showed excellent relationships between area under the curve ratios and drug concentration levels (P>0.002) .Oral Amoxicillin administration in ten healthy volunteers gave maximum concentration peak plasma at two hours and decline through ten hours. Treatment with Iraqi formulation Amoxicillin produced higher area under the curve â€œAUCâ€ and maximum concentration â€œC (max)â€ of Amoxicillin than Indian formulation. Key word: Amoxicillin, Bioequivalence, ODS -DB column.